The OXIMAPA Study: Hypertension Control by ABPM and Association with Sleep Apnea Syndrome by Pulse Oximetry - Maricoto, Tiago (2017)
Introduction: Ambulatory blood pressure monitoring by automatic device is the best blood pressure evaluation method and sleep apnea syndrome is the leading cause of poor control. Oximetry allows screening these individuals but its usefulness has been poorly explored in Primary Health Care. The aim was to evaluate the blood pressure control at the office and with ambulatory blood pressure monitoring by automatic device and to relate it to sleep apnea syndrome.Material and Methods: We selected a sample of 50 participants, representative of 3036 hypertensive patients. The variables were: blood pressure value at the office and blood pressure with ambulatory blood pressure monitoring by automatic device; presence of criteria of sleep apnea syndrome in oximetry.Results: The prevalence of uncontrolled blood pressure was 56% on office evaluation and 68% on ambulatory blood pressure monitoring by automatic device. It was found: 36% of daytime hypertension, 52% nocturnal hypertension, 40% non-dipper profile, 16% of white coat hypertension and 28% masked hypertension. The prevalence of sleep apnea syndrome was 16%. Blood pressure in ambulatory blood pressure monitoring by automatic device and blood pressure in office showed no statistically significant association (p = 0.761). We found a statistically significant association between sleep apnea syndrome and daytime hypertension (p = 0.019) and non-dipper profile (p = 0.005).Discussion and Conclusion: Ambulatory blood pressure monitoring by automatic device detected more 12% of uncontrolled hypertension than office blood pressure. Sleep apnea syndrome is strongly associated with uncontrolled hypertension and oximetry may be a good screening method, but should be studied further.